Pranlukast Antagonizes CD49f and Reduces Stemness in Triple-Negative Breast Cancer Cells - Velázquez-Quesada I; Ruiz-Moreno AJ; Casique-Aguirre D; Aguirre-Alvarado C; Cortés-Mendoza F; de la Fuente-Granada M; García-Pérez C; Pérez-Tapia SM; González-Arenas A; Segura-Cabrera A; Velasco-Velázquez MA (Dove Medical Press, 2020)
Inés Velázquez-Quesada,1,2 Angel J Ruiz-Moreno,1,3,4 Diana Casique-Aguirre,1 Charmina Aguirre-Alvarado,1 Fabiola Cortés-Mendoza,1,5 Marisol de la Fuente-Granada,6 Carlos García-Pérez,7 Sonia M Pérez-Tapia,2,8 Aliesha González-Arenas,6 Aldo Segura-Cabrera,9 Marco A Velasco-Velázquez1,10 1Department of Pharmacology, School of Medicine, Universidad Nacional Autónoma de México, Mexico City, Mexico; 2Research and Development in Bioprocess Unit, National School of Biological Sciences, Instituto Politécnico Nacional, Mexico City, Mexico; 3Graduate Program in Biomedical Sciences, Universidad Nacional Autónoma de México, Mexico City, Mexico; 4Department of Drug Design, Graduate School of Science and Engineering, University of Groningen (RUG), Groningen, The Netherlands; 5Graduate Program in Biochemical Sciences, Universidad Nacional Autónoma de México, Mexico City, Mexico; 6Department of Genomic Medicine and Environmental Toxicology, Institute for Biomedical Research, Universidad Nacional Autónoma de México, Mexico City, Mexico; 7Center for Genomic Biotechnology, Instituto Politécnico Nacional, Reynosa, Tamaulipas, Mexico; 8National Laboratory for Specialized Services of Investigation, Development and Innovation (I+D+i) for Pharma Chemicals and Biotechnological Products, LANSEIDI-FarBiotec-CONACyT, Mexico City, Mexico; 9European Molecular Biology Laboratory, European Bioinformatics Institute, Hinxton, UK; 10Peripherical Unit for Research in Translational Biomedicine, School of Medicine, Universidad Nacional Autónoma de México, Mexico City, MexicoCorrespondence: Marco A Velasco-VelázquezSchool of Medicine, Universidad Nacional Autónoma de México, Circuito Interno s/n, Mexico City 04510, MexicoTel/Fax +52 55 5623 2282Email marcovelasco@unam.mxIntroduction: Cancer stem cells (CSCs) drive the initiation, maintenance, and therapy response of breast tumors. CD49f is expressed in breast CSCs and functions in the maintenance of stemness. Thus, blockade of CD49f is a potential therapeutic approach for targeting breast CSCs. In the present study, we aimed to repurpose drugs as CD49f antagonists.Materials and Methods: We performed consensus molecular docking using a subdomain of CD49f that is critical for heterodimerization and a collection of pharmochemicals clinically tested. Molecular dynamics simulations were employed to further characterize drug-target binding. Using MDA-MB-231 cells, we evaluated the effects of potential CD49f antagonists on 1) cell adhesion to laminin; 2) mammosphere formation; and 3) cell viability. We analyzed the effects of the drug with better CSC-selectivity on the activation of CD49f-downstream signaling by Western blot (WB) and co-immunoprecipitation. Expressions of the stem cell markers CD44 and SOX2 were analyzed by flow cytometry and WB, respectively. Transactivation of SOX2 promoter was evaluated by luciferase reporter assays. Changes in the number of CSCs were assessed by limiting-dilution xenotransplantation.Results: Pranlukast, a drug used to treat asthma, bound to CD49f in silico and inhibited the adhesion of CD49f+ MDA-MB-231 cells to laminin, indicating that it antagonizes CD49f-containing integrins. Molecular dynamics analysis showed that pranlukast binding induces conformational changes in CD49f that affect its interaction with β 1-integrin subunit and constrained the conformational dynamics of the heterodimer. Pranlukast decreased the clonogenicity of breast cancer cells on mammosphere formation assay but had no impact on the viability of bulk tumor cells. Brief exposure of MDA-MB-231 cells to pranlukast altered CD49f-dependent signaling, reducing focal adhesion kinase (FAK) and phosphatidylinositol 3-kinase (PI3K) activation. Further, pranlukast-treated cells showed decreased CD44 and SOX2 expression, SOX2 promoter transactivation, and in vivo tumorigenicity, supporting that this drug reduces the frequency of CSC.Conclusion: Our results support the function of pranlukast as a CD49f antagonist that reduces the CSC population in triple-negative breast cancer cells. The pharmacokinetics and toxicology of this drug have already been established, rendering a potential adjuvant therapy for breast cancer patients.Keywords: CD49f, alpha6 integrin, breast cancer stem cells, pranlukast, drug repositioning, triple-negative breast cancer cells